A polyoxometalate redox flow battery: functionality and upscale. Issue 4 (15th August 2019) - Friedl, Jochen; Pfanschilling, Felix L; Holland-Cunz, Matthäa V; Fleck, Robert; Schricker, Barbara; Wolfschmidt, Holger; Stimming, Ulrich
Abstract: While redox flow batteries carry a large potential for electricity storage, specifically for regenerative energies, the current technology-prone system—the all-vanadium redox flow battery—exhibits two major disadvantages: low energy and low power densities. Polyoxometalates have the potential to mitigate both effects. In this publication, the operation of a polyoxometalate redox flow battery was demonstrated for the polyoxoanions [SiW12 O40 ] 4– (SiW 12 ) in the anolyte and [PV14 O42 ] 9– (PV 14 ) in the catholyte. Emphasis was laid on comparing to which extent an upscale from 25 to 1400 cm 2 membrane area may impede efficiency and operational parameters. Results demonstrated that the operation of the large cell for close to 3 months did not diminish operation and the stability of polyoxometalates was unaltered.